Bottle and breast sucking effects in premature infants - Maria Helena Abud da Silva; Cristina Ide Fujinaga; Adriana Moraes Leite; Andreara de Almeida e Silva; Moacyr Lobo da Costa Junior; Carmen Gracinda Silvan Scochi (Rev Rene)
Feeding a premature infant is a concern when it comes to neonatal care and breastfeeding has been recommended. However, not all services advocates breastfeeding to their patients. The aim of this study was to compare the effects of sucking on the feeding bottle and on the breast regarding the oxygen saturation, skin temperature, heart as well as respiratory rates. Each of the premature infants was its own control, being submitted to bottle suction sections as well as breastfeeding sections. In total, 76 sections of suction were carried out, in which the variables skin temperature, heart and respiratory rates as well as oxygen saturation were monitored. Skin temperature and heart and respiratory rates did not present statistically significant differences. There were important alterations in oxygen saturation, with greater occurrence for feeding bottle. Breast suction was shown to be less stressful than the feeding bottle suction, concerning oxygen saturation.